ACE2 engagement exposes the fusion peptide to pan-coronavirus neutralizing antibodies - Low, Jun Siong; Jerak, Josipa; Tortorici, M Alejandra; Mccallum, Matthew; Pinto, Dora; Cassotta, Antonino; Foglierini, Mathilde; Mele, Federico; Rana Abdelnabi; Weynand, Birgit; Noack, Julia; Montiel-Ruiz, Martin; et al. (bioRxiv, 2022)
Coronaviruses use diverse Spike (S) glycoproteins to attach to host receptors and fuse with target cells. Using a broad screening approach, we isolated from SARS-CoV-2 immune donors seven monoclonal antibodies (mAbs) that bind to all human alpha and beta coronavirus S proteins. These mAbs recognize the fusion peptide and acquire high affinity and breadth through somatic mutations. Despite targeting a conserved motif, only some mAbs show broad neutralizing activity in vitro against alpha and beta coronaviruses, including Omicron BA.1 variant and bat WIV-1, and reduce viral titers and pathology in vivo. Structural and functional analyses show that the fusion peptide-specific mAbs bind with different modalities to a cryptic epitope which is concealed by prefusion-stabilizing 2P mutations and becomes exposed upon binding of ACE2 or ACE2-mimicking mAbs. This study identifies a new class of pan-coronavirus neutralizing mAbs and reveals a receptor-induced conformational change in the S protein that exposes the fusion peptide region. Competing Interest Statement JSL, JJ, FS, AL, ACa are currently listed as an inventor on multiple patent applications, which disclose the subject matter described in this manuscript. AL, DC, FS, JN, MM-R, LAP and DP may hold shares in Vir Biotechnology. The Veesler laboratory and the Sallusto laboratory have received sponsored research agreements from Vir Biotechnology Inc. The other authors declare no competing interests.